DIGITAL TECHNOLOGIES AND ACADEMIC MOBILITY - Atabayeva Kamola Maxmudovna (TRANSMILLIY QO‘SHMA TA’LIM DASTURLARINING RIVOJLANISHI: O‘ZDJTU TAJRIBASI VA XALQARO SIFAT KAFOLATI TIZIMLARI BO‘YICHA ILMIY-AMALIY YONDASHUVLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Academic mobility plays a central role in the internationalization of higher education. In recent years, digital technologies have significantly changed the way students and academic staff participate in exchange programs and international cooperation. This article explores how digital tools influence academic mobility and evaluates their effectiveness in expanding access to global education. The study focuses on both positive outcomes and existing challenges of digital mobility. The findings show that digital technologies reduce financial costs, increase participation rates, and promote intercultural communication. At the same time, issues such as digital inequality and limited face-to-face interaction remain important concerns. The article argues that digital mobility should complement traditional forms rather than replace them.